Recent advances in bacterial outer membrane vesicles: Effects on the immune system, mechanisms and their usage for tumor treatment - Shuo Xiang; Qiufang Yao; Arshad Khan; Dong Wang (Journal of Pharmaceutical Analysis)
Tumor treatment remains a significant medical challenge, with many traditional therapies causing notable side effects. Recent research has led to the development of immunotherapy, which offers numerous advantages. Bacteria inherently possess motility, allowing them to preferentially colonize tumors and modulate the tumor immune microenvironment, thus influencing the efficacy of immunotherapy. Bacterial outer membrane vesicles (OMVs) secreted by gram-negative bacteria are nanoscale lipid bilayer structures rich in bacterial antigens, pathogen-associated molecular patterns (PAMPs), various proteins, and vesicle structures. These features allow OMVs to stimulate immune system activation, generate immune responses, and serve as efficient drug delivery vehicles. This dual capability enhances the effectiveness of immunotherapy combined with chemotherapy or phototherapy, thereby improving anticancer drug efficacy. Current research has concentrated on engineering OMVs to enhance production yield, minimize cytotoxicity, and improve the safety and efficacy of treatments. Consequently, OMVs hold great promise for applications in tumor immunotherapy, tumor vaccine development, and drug delivery. This article provides an overview of the structural composition and immune mechanisms of OMVs, details various OMVs modification strategies, and reviews the progress in using OMVs for tumor treatment and their anti-tumor mechanisms. Additionally, it discusses the challenges faced in translating OMV-based anti-tumor therapies into clinical practice, aiming to provide a comprehensive understanding of OMVs' potential for in-depth research and clinical application.